Prevalence of Hypoglycemia in Patients of Type 2 Diabetes Mellitus - Syed Meerab Javed, Naveed Noor Khan, Waseem Babur, Fayaz Ahmed Memon, Ashhar Arshad, Zille-Huma (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to evaluate the frequency of hypoglycemia in patients of type-2 diabetes mellitus. Study Design:Cross-sectional Place and Duration: King Salman Armed Forces Hospital Tabuk KSA and Muhammed Medical College & Hospital, Mirpurkhas, Sindh during from June, 2020 to Dec, 2020. Methods: There were 115 patients of both genders had type-2 diabetes mellitus were presented.Patients ranged in age from 20 to 60 years old. Individuals participated in the study were asked to sign a permission form acknowledging they had read the information and understood its significance before having their demographic data collected. Frequency of hypoglycemia was recorded by Whipple’s triad questionnaire based information. Symptoms of hypoglycemia were also recorded. SPSS 23.0 was used to analyze all data. Results:Among 115 patients, majority of the patients 65 (56.5%) were males and 50 (43.5%) were females. Mean age of the patients was 51.6±11.54 years and had mean BMI 27.5±8.34 kg/m2. There were 70 (60.9%) cases had rural residency and 45 (39.1%) patients had urban residency.Most common symptoms were dizziness, weakness and sweating among all cases. Metformin was the most common treatment used among all cases, followed by glynase and insulin. We found frequency of hypoglycemia among 50 (43.5%) in which majority of the cases were females. Among 50 cases of hypoglycemia, 11 cases had severe hypoglycemia, 20 cases had moderate and 19 cases had mild hypoglycemia. Conclusion: In this research, we found that type-2 diabetic patients, most of whom were female and rural, had a high incidence of hypoglycemia. The high incidence requires primary care doctors to ask for hypoglycemia symptoms at each diabetes patient visit. It’s also crucial to educate patients about hypoglycemic symptoms and the need of reporting them to alter dosage and avoid recurrence bouts.